(untitled) (GYMNASIUM, 2011)
Dancing contributes at the formation of esthetic education, at the development of artistic ,musical, rhythmic sense, contributes at the fortification of the organism, increase of resistance and efficiency, maintaining feminine grace and characteristics, at educating esthetic motor and represents a manner of socializing of the students. Because artistic dance is an attractive way of plastic movement, elegance and expressivity, valuing beauty and grace through artistically executed moves, we propose its introduction in the physical education lesson, having the same value as sport elements. Considering the introduction of the sports lessons in the first university year, with specialty teachers, we propose the alternation of dance with the other sports categories in the lessons.